A low-cost and water resistant biomass adhesive derived from the hydrolysate of leather waste. Issue 7 (16th January 2017) - Zhou, Jianfei; Xu, Teng; Wang, Xiaoling; Liu, Chang; Liao, Xuepin; Huang, Xin; Shi, Bi
Abstract : A low-cost and water resistant biomass adhesive was prepared by using collagen hydrolysate extracted from leather wastes as the starting material and silane coupling agent as the crosslinking agent. Abstract : A low-cost and water resistant biomass adhesive, collagen hydrolysate–silane coupling agent hybrids (CSH), was prepared by using collagen hydrolysate (CH) extracted from leather waste as the starting material, and silane coupling agent (SCA) as the crosslinking agent. The as-prepared adhesive was fully characterized by Fourier transform infrared spectroscopy (FTIR), 29 Si CP-MAS NMR spectroscopy, differential scanning calorimetry (DSC), scanning electron microscopy (SEM), ANS assay and ninhydrin assay. The as-prepared CSH exhibited pretty good adhesive strength and water resistance. Moreover, the water resistance of CSH can be conveniently tuned by changing the type and dosage of the silane coupling agent. When used as a wood adhesive, the dry adhesive strength of CSH was as high as 1.57 MPa, and the corresponding wet adhesive strength reached 0.95 MPa. Our experimental results suggest that the collagen hydrolysate extracted from leather waste has a great potential to be used as a low-cost and highly effective adhesive in the wood composite industry.